Amino acid score of some products for younger school children nutrition - Vatan, M.; Babienko, V. (Journal of Education, Health and Sport, 2023)
Introduction. Wholesome nutrition is one of the most important factors in shaping a person’s somatic and mental health. Eating habits are formed in childhood and consolidated in adulthood. They can also have an impact on the development of future chronic diseases, such as metabolic syndrome, type 2 diabetes, cardiovascular diseases. The purpose of the work is to evaluate the amino acid score of the main food products of children of primary school age. Material and methods. The research was carried out during 2016 - 2021. Food menus for 1000 of children aged 6-9 years old living in the South of Ukraine (cities Odessa and Mykolaiv, suburban villages and villages far from the regional centres). The study was carried out during the spring-summer (May-June) and autumn-winter (November-December). Field studies of the amino acid content in 24 products, which were included in the first two deciles in terms of frequency of consumption, were also conducted. The results. The distribution of food products was marked by a certain constancy and depended little on the season of the year. Most foods are a major source of carbohydrates. Only 8 out of 24 products were a source of protein and essential amino acids. The overall consumption of protein-rich foods by younger schoolchildren was low. Conclusion. Children 6-10 years old should consume protein in the amount of 0.95 g/kg/day. Our research shows that even such an understated standard of need may not be fulfilled under the current state of affairs. The main sources of protein for children of primary school age in Southern Ukraine are milk, cheese, chicken, river fish and legumes. Dairy products, eggs and chicken have the highest value in terms of amino acid content, and pork has the lowest value. Legumes have a high amino acid content, but they are inferior to products of animal origin.